Coal fly ash amendment: affecting soil resistance, water retention, and root growth in sandy soils - Jubaedah, Jubaedah; Iskandar, Iskandar; Baskoro, Dwi Putro Tejo; Mulyanto, Budi; Nurida, Neneng Laela; Yustika, Rahmah Dewi; Maswar, Maswar (Journal of Degraded and Mining Lands Management, 2025)
Studies have shown that coal fly ash (CFA) can improve soil physical properties (such as bulk density) and increase available water content. However, its pozzolanic properties may also contribute to soil compaction. The overall impact of these contrasting effects on soil behavior remains insufficiently understood. This study investigated the effects of CFA amendment on soil resistance, water retention, and corn root growth in sandy soil. Using a completely randomized design, the research was conducted at the Taman Bogo Agricultural Station in East Lampung for two planting seasons (October 2022 - June 2023). Four CFA rates (0%, 3%, 6%, and 12% w/w) were applied in lysimeter plots with five replications. The results demonstrated that CFA application reduced soil bulk density (BD) at 6% and 12% rates due to CFA’s lower BD than the soil. However, higher CFA doses increased soil penetration resistance (PR), likely due to surface crust formation rather than pozzolanic reactions. Plant available water capacity (PAWC) significantly increased by 6% and 12% CFA, thus improving soil water retention. Improving physical properties in the second season promoted root growth at the 12% CFA rate. The use of CFA in sandy soils leads to improvement in selected physical properties and enhances water retention. Therefore, while CFA enhances water retention, its effects on soil compaction and root growth must be carefully managed to ensure optimal results.